2011
DOI: 10.1007/s12272-011-0917-2
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of heme oxygenase-1 induction in inhibitory effect of ethyl gallate isolated from Galla Rhois on nitric oxide production in RAW 264.7 macrophages

Abstract: In the present study, we investigated an anti-inflammatory effect of ethyl gallate (EG) isolated from Galla Rhois as evaluated by inhibition of nitric oxide (NO) production and inducible nitric oxide synthase (iNOS) expression, and a potential role of heme oxygenase-1 (HO-1) in the inhibition of NO production elicited by EG. Treatment of RAW264.7 macrophages with EG significantly inhibited the production of NO and iNOS expression stimulated by lipopolysaccharide (LPS). We also demonstrated that EG treatment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…We observed previously that inhibition of ERK1/2, Akt and JNK reduced Nrf2 mediated transcription in astrocytes [17,21]. This is in accord with a recent report showing that LPS stimulated expression of HO-1, a down-stream product of Nrf2 transcription, involved Akt and ERK1/2 activation [23]. In the present study the levels of phosphorylated/activated Akt were increased 24 h after LPS exposure (JNK was below detection limit and ERK1/2 too variable).…”
Section: Discussionsupporting
confidence: 90%
“…We observed previously that inhibition of ERK1/2, Akt and JNK reduced Nrf2 mediated transcription in astrocytes [17,21]. This is in accord with a recent report showing that LPS stimulated expression of HO-1, a down-stream product of Nrf2 transcription, involved Akt and ERK1/2 activation [23]. In the present study the levels of phosphorylated/activated Akt were increased 24 h after LPS exposure (JNK was below detection limit and ERK1/2 too variable).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, compounds 2 and 3 decreased the nitric oxide (NO) production in macrophages with IC 50 values of 7.0 and 7.5 μg/mL, respectively (Table 2). These data are consistent with the previous studies, which reported that methyl gallate and ethyl gallate inhibited NO production and iNOS expression in macrophages stimulated by LPS [22][23]. On the other hand, these two compounds (2,3) did not show any inhibition of NF-κB in PMA induced chondrocytes, as shown in Table 2.…”
supporting
confidence: 92%
“…[ 6 7 8 9 10 11 ] Methyl gallate and ethyl gallate isolated from GR were also found to exert significant anti-inflammatory activity in lipopolysaccharide-stimulated RAW264.7 macrophages through the induction of heme oxygenase-1 and the suppression of inducible nitric oxide synthase/cyclooxygenase-2 (COX-2). [ 12 13 ] Moreover, galloylglucose (GG6-10) isolated from GR inhibited the invasion of metastatic HT-1080 cells into a reconstituted basement membrane through inhibition of gelationolysis mediated by matrix metallopeptidase (MMP-2) and MMP -9, whereas the ellagic acid extracted from GR showed anticancer activity against nasopharyngeal carcinoma cells through downregulated expression of COX-2 and stathmin. [ 14 15 ] Furthermore, oral administration of GR 85% methanol extract reduced brain infarct volume by 37.5% and lipid peroxidation in middle cerebral artery occlusion, while also improving sensory motor function in a transient focal cerebral ischemia rat model.…”
Section: Introductionmentioning
confidence: 99%